2016
DOI: 10.1007/s10620-016-4257-4
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of Statin Therapy Among Patients with NAFLD in the USA: Validation with Big Data

Abstract: We read with interest the article by Blais et al. [1] recently published in the Journal. In an analysis of a random sample of 255 patients with Nonalcoholic Fatty Liver Disease (NAFLD) in the Veteran Affairs (VA) hospital system with dyslipidemia, only 152 (59.6 %) were on statin therapy. We sought to validate these findings in larger, non-VA hospital systems in the USA. Additionally, because women are greatly underrepresented in the VA cohort (5 %), we sought to identify gender differences in statin use.We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In the evaluation of hepatocellular damage, aminotransferase alterations were observed in the animals that received the MCD diet. There are reported cases of statin-related hepatotoxicity, but although elevated aminotransferases are not uncommon in patients receiving statins, serious liver injury from statins is rarely seen in clinical practice [27]. The use of SIM in animals with NASH reduced the levels of these enzymes and reduced the hepatocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of hepatocellular damage, aminotransferase alterations were observed in the animals that received the MCD diet. There are reported cases of statin-related hepatotoxicity, but although elevated aminotransferases are not uncommon in patients receiving statins, serious liver injury from statins is rarely seen in clinical practice [27]. The use of SIM in animals with NASH reduced the levels of these enzymes and reduced the hepatocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…This database has been used and validated in different fields of medicine, including gastroenterology. (3)(4)(5) We identified patients with pharmacy data who are at least 50 years old seen at participating institutions from 1999 to 2016. Similarly to Choi et al, we identified diagnoses of cholangiocarcinoma using International Classification of Diseases, Ninth Revision, as follows: 155.1, 156.1, 156.2, 156.8, and 156.9.…”
Section: To the Editormentioning
confidence: 99%
“…Plausible explanations include underdiagnosis of these diseases and failure to accurately record them during inpatient admissions. This, however, should not affect the results of our study as previous studies from this database have been published and validated against studies from other databases [24,25,49]. Certain risk factors such as HLA haplotypes (especially for AIH, PBC and PSC cohorts), family history and the impact of pharmacological interventions (such as corticosteroid use in case of NAFLD) could not be assessed.…”
Section: Discussionmentioning
confidence: 99%